Optimizing megakaryocyte polyploidization by targeting multiple pathways of cytokinesis - Avanzi, Mauro P.; Chen, Amanda; He, Wu; Mitchell, W. Beau (Transfusion (Philadelphia, Pa.), 2012)
BACKGROUND: Large‐scale in vitro production of platelets (PLTs) from cord blood stem cells is one goal of stem cell research. One step toward this goal will be to produce polyploid megakaryocytes capable of releasing high numbers of PLTs. Megakaryocyte polyploidization requires distinct cytoskeletal and cellular mechanisms, including actin polymerization, myosin activation, microtubule formation, and increased DNA production. In this study we variably combined inhibition of these principal mechanisms of cytokinesis with the goal of driving polyploidization in megakaryocytes. STUDY DESIGN AND METHODS: Megakaryocytes were derived from umbilical cord blood and cultured with reagents that inhibit distinct mechanisms of cytokinesis: Rho‐Rock inhibitor (RRI), Src inhibitor (SI), nicotinamide (NIC), aurora B inhibitor (ABI), and myosin light chain kinase inhibitor (MLCKI). Combinations of reagents were used to determine their interactions and to maximize megakaryocyte ploidy. RESULTS: Treatment with RRI, NIC, SI, and ABI, but not with MLCKI, increased the final ploidy and RRI was the most effective single reagent. RRI and MLCKI, both inhibitors of MLC activation, resulted in opposite ploidy outcomes. Combinations of reagents also increased ploidy and the use of NIC, SI, and ABI was as effective as RRI alone. Addition of MLCKI to NIC, SI, and ABI reached the highest level of polyploidization. CONCLUSION: Megakaryocyte polyploidization results from modulation of a combination of distinct cytokinesis pathways. Reagents targeting distinct cytoskeletal pathways produced additive effects in final megakaryocyte ploidy. The RRI, however, showed no additive effect but produced a high final ploidy due to overlapping inhibition of multiple cytokinesis pathways.